Dual Mode Photocurrent Generation of Graphene-Oxide Semiconductor Junction. (1st January 2015) - Jeong, Heejeong; Heo, Jinseong; Kyoung, Jisoo; Baik, Chan-Wook; Park, Seongjun; Hwang, Sung Woo; Lee, Chang-Won
Abstract : The need for low-cost and highly versatile photosensing devices keeps increasing. In this work, we present a heterojunction device based on wafer-scale graphene grown by chemical vapor deposition (CVD) and sputtered InGaZnO (IGZO) semiconductor for dual mode photocurrent collection. The photocurrent can be collected either from the lateral gold/graphene/gold configuration or from the vertical graphene/IGZO/nickel heterojunction configuration with no external bias. Incident-energy-dependent photocurrent scanning microscopy shows that the dominant photocarriers are formed at the edge of the gold electrode through photo-thermoelectric hot hole generation in the lateral configuration. Vertical mode renders unidirectional current flow by photoexcited electrons in the IGZO and the subsequent relaxation and diffusion due to Fowler-Nordheim potential.